The Impact of the CLT Approach in Developing English Language Skills among Saudi EFL Students: Students’ Perceptions - Hakami, Adeeb (European Scientific Journal, ESJ, 2025)
This study examines Saudi EFL students’ perceptions of the Communicative Language Teaching (CLT) approach and its impact on developing the four core English skills: listening, speaking, reading, and writing. Using a qualitative research design, data were collected via semi-structured interviews and focus group discussions with 30 purposively sampled participants from Taif University, representing diverse educational backgrounds and regions (urban and rural). Thematic analysis was employed to uncover key patterns in the data. The findings reveal that CLT significantly enhanced students’ engagement and fluency, particularly in listening and speaking. However, challenges such as insufficient teacher preparedness, resource disparities between urban and rural settings, and linguistic anxiety were identified. STEM students demonstrated higher acceptance of CLT, likely due to their familiarity with interactive learning, whereas rural students faced more difficulties adapting to the student-centered approach. To address these challenges, the study underscores the necessity of comprehensive teacher training programs, curriculum reforms incorporating digital tools, and strategies to alleviate students’ linguistic anxiety. Future research should explore the long-term effects of CLT implementation and the potential of blended learning approaches within Saudi EFL contexts.